2011
DOI: 10.1038/ja.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Verticillin A is likely not produced by Verticillium sp.

Abstract: COMMUNICATION TO THE EDITORVerticillin A is likely not produced by Verticillium sp.The Journal of Antibiotics (2011) 64, 523-524; doi:10.1038/ja.2011; published online 27 April 2011Verticillin A is a fungal epipolythiodioxopiperazine (ETP) metabolite with antibiotic properties, which was originally reported to be produced from Verticillium sp. 1 It is structurally very similar to Chaetocin from Chaetomium minutum, differing only in the position of two hydroxyl groups (Figure 1). Chaetocin is the first describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The discovery that a significant number of diketopiperazines that were previously described as being sourced from fungi can be also produced by CDPSs in bacterial strains evidences that the sourcing organism of some of these metabolites can frequently be difficult to ascribe, and that taxonomically distant species can produce similar diketopiperazine dimers [34,182]. For example, and as mentioned by Schenke et al [183], the isolation of verticillin A ( 13 ) from cultures of a strain of Gliocladium roseum , a mycoparasite of Verticillium , evidenced that the original fungal source might have been confused with another fungus or contaminated with a Gliocladium colonist. It is also interesting to observe that while originally reported from a marine strain of an Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that a significant number of diketopiperazines that were previously described as being sourced from fungi can be also produced by CDPSs in bacterial strains evidences that the sourcing organism of some of these metabolites can frequently be difficult to ascribe, and that taxonomically distant species can produce similar diketopiperazine dimers [34,182]. For example, and as mentioned by Schenke et al [183], the isolation of verticillin A ( 13 ) from cultures of a strain of Gliocladium roseum , a mycoparasite of Verticillium , evidenced that the original fungal source might have been confused with another fungus or contaminated with a Gliocladium colonist. It is also interesting to observe that while originally reported from a marine strain of an Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…For verticillin producing strains, there has been some confusion on the fungal taxonomy [ 13 ]. Earlier studies on the chemistry of verticillin analogues have identified the verticillin-producing fungi as belonging to the genera Gliocladium, Penicillium, and Verticillium [ 36 , 37 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…contaminated with a morphologically similar mycoparasite such as Clonostachys rosea. [179] In agreement, in 2017, the ver gene cluster encoding the enzymatic machinery for verticillin production in Clonostachys rogersoniana -a parasitic fungus related to C. rosea -was published. [143] For 12 out of the 13 genes, a role in verticillin A formation could be proven by single-gene deletions (Figure 8).…”
Section: Verticillinsmentioning
confidence: 93%
“…Probably, verticillin A was isolated from a sample containing Verticillium sp. contaminated with a morphologically similar mycoparasite such as Clonostachys rosea [179] …”
Section: Epipolythiodioxopiperazines: Bridging the Ringmentioning
confidence: 99%